Highlights of the Romanian Perspective of Datio in Solutum for Consumer Borrowers - Codrin Macovei (Tilburg Law Review, 2019)
In 2016, the Romanian Parliament voted on the final version of the 'datio in solutum' law (Law No. 77/2016 'on the' datio in solutum 'of real estate in order to settle the obligations assumed by credits'), allowing the borrowers to fully settle their liability by transferring to the banks the ownership right over mortgages used as collateral for loans. The final version of the law includes some important restrictions: the ‘First Home’ governmental program was excluded from the jurisdiction of the law, a ceiling amounting to the equivalent of 250,000 EUR on the size of the loan at time of origination was set and the law only applied for mortgages that qualify as dwellings and were contracted by ‘consumers’. However, the law would apply to all existing contracts (retroactive applicability).1 This article analyzes 'datio in solutum' from the Romanian perspective, a new approach in the national legal system that already made the object of the constitutional control by a number of decisions. We will also review the solutions of Spanish and French legal systems regarding these particular consumer protection problems.